Two short peptides including segments of subunit A of Escherichia coli DNA gyrase as potential probes to evaluate the antibacterial activity of quinolones - Marchetto, Reinaldo [UNESP]; Nicolás, Ernesto; Castillo, Núria; Bacardit, Jordi; Navia, Margarita; Vila, Jordi; Giralt, Ernest (Wiley, 2001)
Quinolones constitute a family of compounds with a potent antibiotic activity. The enzyme DNA gyrase, responsible for the replication and transcription processes in DNA of bacteria, is involved in the mechanism of action of these drugs. In this sense, it is believed that quinolones stabilize the so-called 'cleavable complex' formed by DNA and gyrase, but the whole process is still far from being understood at the molecular level. This information is crucial in order to design new biological active products. As an approach to the problem, we have designed and synthesized low molecular weight peptide mimics of DNA gyrase. These peptides correspond to sequences of the subunit A of the enzyme from Escherichia coli, that include the quinolone resistance-determining region (positions 75-92) and a segment containing the catalytic Tyr-122 (positions 116-130). The peptide mimic of the non-mutated enzyme binds to ciprofloxin (CFX) only when DNA and Mg2+ were present (Kd = 1.6 × 10 -6 m), a result previously found with DNA gyrase. On the other hand, binding was reduced when mutations of Ser-83 to Leu-83 and Asp-87 to Asn-87 were introduced, a double change previously found in the subunit A of DNA gyrase from several CFX-resistant clinical isolates of E. coli. These results suggest that synthetic peptides designed in a similar way to that described here can be used as mimics of gyrases (topoisomerases) in order to study the binding of the quinolone to the enzyme-DNA complex as well as the mechanism of action of these antibiotics. Copyright © 2001 European Peptide Society and John Wiley & Sons, Ltd.
Keywords: Affinity chromatography; DNA gyrase; Escherichia coli; Peptide design; Peptide synthesis; Quinolones; Solid phase; Topoisomerases; asparagine; aspartic acid; bacterial DNA; bacterial enzyme; ciprofloxacin; DNA topoisomerase (ATP hydrolysing); leucine; magnesium ion; quinolone derivative; serine; synthetic peptide; tyrosine; alpha chain; amino acid sequence; antibacterial activity; antimicrobial activity; bacterium isolate; catalysis; DNA replication; DNA transcription; drug binding; drug design; drug mechanism; drug resistance; drug synthesis; enzyme subunit; gene mutation; molecular biology; molecular mimicry; molecular weight; nonhuman; priority journal; Anti-Infective Agents; Binding Sites; Chromatography, Affinity; Ciprofloxacin; DNA Topoisomerases, Type II; Drug Design; Molecular Probes; Mutation; Peptides; Spectrometry, Fluorescence